THE EFFECT OF THE INTERNET OF THINGS INTEGRATED DISCOVERY LEARNING MODEL ON STUDENTS CRITICAL THINKING SKILLS - Abdullah Ardi; Hardiansyah Ma'sum; Mohammad Edy Nurtamam; Alkadri Ajwan; Daniel Pasaribu; Tomi Apra Santosa (International Journal of Teaching and Learning, 2023)
The purpose of this study was to determine the effect of the Internet of Things integrated discovery learning model on students' critical thinking skills. This study is a meta-analysis study. The data source comes from an analysis of 9 national and international journals. The process of tracing data sources through Google Scholar, Proquest, EBSCO, DOAJ, and ERIC databases. Data source selection technique through PRISMA method. The inclusion criteria in this study are research published in 2020-2023, SINTA and Scopus indexed research, research using experimental methods, and research must have a sample of 20 students. Data analysis in this study calculated the value of effect size, heterogeneity, summary effect size and publication bias with the help of JASP application. The results of this study concluded the average value of effect size of ( ES = 1.06) high criteria. These findings explain that there is a significant influence of the Internet of Things integrated discovery learning model on students' critical thinking skills.